The Synthesis of Warfarin Using a Reconfigurable‐Reactor Platform Integrated to a Multiple‐Variable Optimization Tool. Issue 67 (12th November 2020) - Kwak, Jee Seong; Bizarri, Nour; Sharif, Sepideh; Zhang, Wenyao Peter; Mallik, Debasis; Organ, Michael G.
Abstract: Optimization of the asymmetric synthesis of warfarin, an important anticoagulant, has been evaluated using a reconfigurable reaction platform capable of performing batch, continuous flow, and plug‐flow synthesis. Further, this platform has been integrated with a novel, multidimensional, multiple variable analysis tool that can evaluate multiple critical quality attributes (CQA), percent conversion and enantiomeric excess in this case, from a single injection that is repeatedly recycled in a closed loop of chromatography columns, a detector and a heart‐cut valve. Further, the new, integrated analysis system also facilitates validation of each QA, providing a high‐level of confidence in analytical measurements, which are obtained without operator intervention. Abstract : Doing much more chemistry, much faster : An integrated, reconfigurable‐reactor, multi‐dimensional chromatography platform for multiple‐reaction‐attribute optimization has been invented. Without ever leaving the sampling/analysis component, a single reaction sample can be evaluated for two or more attributes in unique chromatographic dimensions and each result validated by re‐purposing the peak of interest back through the same (or another) column.